2012
DOI: 10.1111/nph.12091
|View full text |Cite
|
Sign up to set email alerts
|

Medicago truncatula DNF2 is a PIPLCXD‐containing protein required for bacteroid persistence and prevention of nodule early senescence and defense‐like reactions

Abstract: Summary Medicago truncatula and Sinorhizobium meliloti form a symbiotic association resulting in the formation of nitrogen‐fixing nodules. Nodule cells contain large numbers of bacteroids which are differentiated, nitrogen‐fixing forms of the symbiotic bacteria. In the nodules, symbiotic plant cells home and maintain hundreds of viable bacteria. In order to better understand the molecular mechanism sustaining the phenomenon, we searched for new plant genes required for effective symbiosis. We used a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
138
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 64 publications
(105 reference statements)
12
138
2
Order By: Relevance
“…Phenotypic characterization suggests that dnf4 causes problems in the symbiosis at stages later than other dnf mutants, such as dnf1, dnf2, and dnf5, because a number of late symbiotic genes from bacteria (nodF, bacA and nifH) and plants (LB1, CAM1 and Nodulin 31) are still expressed in dnf4 (12). This classification is supported by our microscopic analyses demonstrating that differentiating bacteroids are present in dnf4 mutant nodules, in contrast to those of dnf1 and dnf2, in which the bacteroids barely differentiate (6,13). Furthermore, PI staining of differentiated bacteroids in the dnf4 mutant suggests that NCR211 functions to maintain the viability of differentiating bacteroids.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Phenotypic characterization suggests that dnf4 causes problems in the symbiosis at stages later than other dnf mutants, such as dnf1, dnf2, and dnf5, because a number of late symbiotic genes from bacteria (nodF, bacA and nifH) and plants (LB1, CAM1 and Nodulin 31) are still expressed in dnf4 (12). This classification is supported by our microscopic analyses demonstrating that differentiating bacteroids are present in dnf4 mutant nodules, in contrast to those of dnf1 and dnf2, in which the bacteroids barely differentiate (6,13). Furthermore, PI staining of differentiated bacteroids in the dnf4 mutant suggests that NCR211 functions to maintain the viability of differentiating bacteroids.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, dnf4 bacteroids, including ones staining positive for PI, appeared elongated and differentiated (Fig. 2D), unlike other early-stage mutants (6,13), although the degree of bacteroid differentiation was unclear. Coupling PI staining with SYTO9, a commonly used viability dye, yielded a similar pattern.…”
Section: Resultsmentioning
confidence: 99%
“…proportion of ern2 nodules (Hossain et al, 2006;Kumagai et al, 2007;Pislariu et al, 2012;Bourcy et al, 2013;Berrabah et al, 2014). It has also been suggested that nodule senescence can be triggered by the host to avoid the energetic cost of maintaining ineffective nodules (Suganuma et al, 2003;Magori and Kawaguchi, 2009).…”
Section: Mild Infection Defects May Contribute To the Accelerated Senmentioning
confidence: 99%
“…Tnt1 was used to generate approximately 12,000 independent lines that represent over 300,000 insertions in M. truncatula (Tadege et al, 2008;Cheng et al, 2011). Many M. truncatula genes have been identified through forward and reverse genetics approaches using the Tnt1 retrotransposon insertion population (Pang et al, 2009;Zhao et al, 2010;Laurie et al, 2011;Tadege et al, 2011;Zhou et al, 2011;Cheng et al, 2012;Bourcy et al, 2013).…”
mentioning
confidence: 99%